Analisis Undang-Undang PKDRT Dalam Relasi Hukum Keluarga Kontemporer Tahir Mahmood - Sar'an, Mohamad; Hidayatulloh, Yusuf; Albana, Rifki Hasan; Athaillah, Muhammad Farhan; Fauzi, Muhammad Rezky (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This research aims to analyze the law on the elimination of domestic violence (PKDRT) in Tahir Mahmood's contemporary family law relations. Related to the methodology used in this research is normative juridical using qualitative data types of library research and content analysis using a descriptive analysis approach method. The results of the study show that victims of criminal acts of domestic violence are not unwilling to report the crimes of the perpetrators, but there are external forces that prevent them from reporting, one of which is the moral burden on the family and the patriarchal culture is still quite thick. Then law enforcement officials need to provide penalties that provide a deterrent effect to perpetrators of domestic violence in the process of implementing regulations so that the same mistakes are not repeated because if it ends in a peaceful way and is resolved in a family manner, there will be no significant results in providing security to victims because it is not justified regarding the implementation of Law number 23 of 2004 concerning PKDRT. Tahir Mahmood's methodology is one of the steps to reform the PKDRT law because it is in accordance with the situation of maslahat conditions and is relevant to the Indonesian state.